Isolation and prevalence of' pathogenic leptospira interrogans in slaughtered cattle in two abattoirs i n southwestern Nigeria (2011)
Leptospirosis is a waterborne bacterial disease, transmitted to humans through contaminated water, usually by urine of rodents that are chronically infected by the pathogenic strains.The prevalence and incidence of leptospirosis in slaughtered cattle in relation to the risk of exposure of abattoir workers and the public consumers was determined in this study. The objective of this study ;was to evaluate the prevalence of bovine leptospirosis in slaughtered cattle in southwestern Nigeria. Kidney samples from 108 cattle were examined. Samples were .collected from Bodija abattoir in Ibadan, capital city of ;0yo State, and Lafenwa abattoir in Abeokuta, capital city :of Ogun State. Leptospira was isolated in Ellinghausen- McCullough-Johnson-Harris broth medium (EMJH). Pathogenecity test was carried out in Guinea pigs. Gross 'and histopathological lesions were observed in their kidneys. Leptospira species were isolated from 89 (82.4%) out of 108 kidneys from the slaughtered cattle. Twenty (95.2%) out of 21 kidneys and 69 (79.3%) out of 87 kidneys collected from Ibadan and Abeokuta respectively were positive. Only 31 (28.7%) (9 kidneys from Ibadan and 22 from Abeokuta) kidneys showed visible macroscopic changes, while histomorphological changes such as interstitial nephritis, tubular nephrosis and tubular protein cast were observed. Death of guinea pigs that were inoculated occurred within 24 hours to 168 hrs. The isolation of ieptospira interrogans and the pathology associated with kidneys obtained in this study indicates that cattle slaughter in public abattoir in South-western Nigeria may be sources of exposure and infection to abattoir workers and the public to leptospirosis